A zero crossing PWM controller of a full bridge single phase synchronous inverter for microgrid systems - Rahaman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (International Journal of Engineering and Information Systems (IJEAIS), 2017)
The controlling method of microgrid connected inverter is complicated. Therefore, researchers have designed a different way to improve the control system. Improving the control system by synchronizing the phase is still a critical issue. This paper introduces a zero crossing with the aid of PWM technique to synchronize the microgrid frequency and phase, decreased ripple noise while forced discrete mode provides low output ripple current. Besides, to reduce the ripple current and phase synchronized with same phase and frequency, an LC lowpass filter has been used in input and output on both sides of the inverter. Designed inverter is validated through simulations using Matlab 2016a. Two parameters, a balanced resistive load of star configuration (RL = 20.5 Ω) and input DC voltage, ± 35V are considered. The initial parameters of the design are phase angle of 0 degree, switching frequency of 1.65kHz, microgrid frequency of 50 Hz and cut-off frequency of 33Hz. Simulated results indicate that the designed inverter has better performance regarding with overall efficiency of 96.01% and phase angle of only 3.450. . Therefore, it is expected that the proposed design will improve the performance of microgrid system.